Characterization of kraft lignin from Pinus pinaster - Duarte, Ana Paula (2010)
This paper presents the results about the lignin from Pints pinaster, the only softwood used in Portuguese pulp and paper industries. Six samples of lignin were collected and studied. The first three samples were precipitated from kraft black liquors at different H-factors. using conventional batch pulping. The other three corresponded to the lignin obtained from black liquors of flow-through reactor at the same H-factors. The residual sugars from the lignin obtained were hydrolysed according to the trifluoroacetic acid method and quantified by HPLC. The main residual sugars on the lignin samples from both reactors were found to be xylose, galactose and arabinose, which indicates that the lignin-carbohydrate linkages are similar to other common softwoods. The elemental analyses of these samples showed that, in the initial stage of delignification, the HS' anions are strongly involved in the delignification mechanism. It was also shown that the C/H ratio was relatively constant, which indicated the weak participation of condensation reactions. The infrared spectra of these samples evidenced the presence of the main peaks corresponding to different functional groups of softwood lignin structure. They also showed that the content of conjugated carbonyl groups decreased with the reaction time. Finally, the permanganate potassium oxidation of the lignin samples showed the presence of the principal fragments present in softwood lignin. It was also shown that. when the time of delignification increased, the amount of non-condensed units decreased, whereas that corresponding to condensed ones increased.